2020
DOI: 10.1007/s00268-020-05661-5
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Analysis and Internal Validation to Predict the Risk of Cystobiliary Communication in Patients Undergoing Hydatid Liver Cyst Surgery

Abstract: Purpose Biliary leakage caused by cystobiliary communication (CBC) is a common clinical concern. This study sought to identify predictors of CBC in hepatic cystic echinococcosis (HCE) patients undergoing hydatid liver cyst surgery and establish nomograms to predict CBC. Methods A predictive model was established in a training cohort of 310 HCE patients diagnosed between January 2013 and May 2017. Upon revision of the records of clinical parameters and imaging features of these patients, the lasso regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…All subjects ( n = 1749) were randomly divided into two groups using the R package caret: the development cohort (67%, n = 1165) and the validation cohort (33%, n = 584). It has been proven suitable to include 2/3–4/5 patients as the development cohort ( 17 , 18 ). The baseline values of the total cohort and the development cohort are displayed in Table 1 , according to whether CAA was present.…”
Section: Resultsmentioning
confidence: 99%
“…All subjects ( n = 1749) were randomly divided into two groups using the R package caret: the development cohort (67%, n = 1165) and the validation cohort (33%, n = 584). It has been proven suitable to include 2/3–4/5 patients as the development cohort ( 17 , 18 ). The baseline values of the total cohort and the development cohort are displayed in Table 1 , according to whether CAA was present.…”
Section: Resultsmentioning
confidence: 99%
“…After the inclusion and exclusion criteria, there were 152 non-LAA stroke patients were admitted to the study. In previous studies, it is common and suitable to include 2/3–4/5 patients as the development group (Gao et al 2020 ; Du 2020 ; Wang 2020 ; Guan 2019 ). In our study, we used R (packge caret) to randomly select 2/3 of the patients as the development group, and the remaining patients as the validation group.…”
Section: Methodsmentioning
confidence: 99%
“…[ 27 ] Radical approaches such as total, subtotal, or partial pericystectomy have as a goal the removal of the cyst with a rim of surrounding liver parenchyma. [ 1 , 2 , 5 , 28 , 31 ] The ideal surgical treatment of liver hydatid cysts remains a matter of debate. [ 12 , 32 ] In a recent meta-analysis, Pang et al demonstrated that radical procedures reduce the rates of postoperative complications and cyst recurrence when compared to conservative surgery.…”
Section: Discussionmentioning
confidence: 99%